Epoxy resin surface functionalization using atmospheric pressure plasma jet treatment - Sangprasert W. (2014)
Atmospheric pressure plasma jet (APPJ) of N2 has been applied to promote adhesion between the epoxy resin post and composite core material due to the chemical active functional groups created. The APPJ was proved to be able to improve adhesive ability of the epoxy resin through the polar groups such as carbonyl group on its surface revealed by decreasing contact angle. The jet was generated from N2/Ar and N2/He gas mixture with ratio as low as 0.40-0.44 vol %, respectively. The optical emission spectrometry showed that the active species which could react with the substrate surface are nitrogen molecules and nitrogen molecules ion. The radial distribution functions (RDFs) calculations indicated that the most probable position of nitrogen active species reacting on the epoxy surface is at hydroxyl group with hydrogen bonding distance less than 35 nm. © 2012 The Japan Society of Applied Physics.